Screening and identification indigenous yeast from neera Siwalan for bioethanol production. (February 2019) - Widyaningrum, T; Suharjono,; Ardyati, T; Aulanni'am,
Abstract: The main energy source commonly used by the community comes from fossil energy, especially petroleum. The energy crisis shows that Indonesia's fossil energy reserves are limited. Based on this fact, it is important to develop alternative energy that is environmentally friendly and sustainable, for example bioethanol. The purpose of this research is to screening and identify indegenous yeast from neera siwalan which is potential for bioethanol production. Isolation of yeast from neera siwalan is done using coconut medium. Purification is done to get one pure isolate. Screening is done by observing several parameters: the level of bioethanol production (using an alcohol meter), the content of reducing sugar with the DNS method, and the number of cells with optical density (600nm). Identification is done using ITS 4 and ITS 5. Based on the results of screening, four yeast isolates were produced, namely S3D, S1A, S2D, S1C. Based on these results the superior isolates producing bioethanol are S1A (14.4%). The results of the identification showed that the isolate was similar to Candida tropicalis with 100% similarity value.